2019
DOI: 10.1042/bsr20181584
|View full text |Cite
|
Sign up to set email alerts
|

Fluoxetine suppresses inflammatory reaction in microglia under OGD/R challenge via modulation of NF-κB signaling

Abstract: We aimed to investigate the anti-inflammatory role of fluoxetine, a selective serotonin reuptake inhibitor, in microglia (MG) and the mechanisms under oxygen glucose deprivation/reoxygenation (OGD/R). An OGD/R model on BV-2 cells was used for the study of microglia under ischemia/reperfusion injury in ischemic stroke. Lentiviral transfection was applied to knock down IκB-α. Enzyme-linked immunosorbent assay (ELISA) was used for detecting levels of TNF-α, IL-1β, and IL-6, and real-time PCR was used to assess th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 42 publications
0
21
0
Order By: Relevance
“…Even though both fluoxetine and ARA290 inhibited chronic stress-induced peripheral inflammation and microglia activation, the two drugs showed different effects on the expression of inflammatory cytokines, suggesting that the two drugs inhibit inflammation through different mechanisms. It has been reported that fluoxetine inhibits NF-κB activation in microglia/macrophages ( Tian et al, 2019 ) and works as a direct NLRP3 inhibitor to limit inflammasome activation ( Ambati et al, 2021 ). On the other hand, several studies have revealed that EPO induces microglia/macrophage polarization toward M2 whereas such a role was not found for fluoxetine ( Wang et al, 2017 ; Wei et al, 2017 ; Gu et al, 2021 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Even though both fluoxetine and ARA290 inhibited chronic stress-induced peripheral inflammation and microglia activation, the two drugs showed different effects on the expression of inflammatory cytokines, suggesting that the two drugs inhibit inflammation through different mechanisms. It has been reported that fluoxetine inhibits NF-κB activation in microglia/macrophages ( Tian et al, 2019 ) and works as a direct NLRP3 inhibitor to limit inflammasome activation ( Ambati et al, 2021 ). On the other hand, several studies have revealed that EPO induces microglia/macrophage polarization toward M2 whereas such a role was not found for fluoxetine ( Wang et al, 2017 ; Wei et al, 2017 ; Gu et al, 2021 ; Wang et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of HDAC3 activity following miR-193b-3p treatment reduced expression levels of these inflammatory cytokines in vivo. NF-κB should be a transcription factor of inflammatory mediators that plays a key role in neuroinflammation [46,47]. MiR-193b-3p significantly increased NF-κB p65 acetylation and reduced its transcriptional activity after SAH, suggesting that miR-193b-3p exerts neuroprotective effects.…”
Section: Discussionmentioning
confidence: 99%
“…in experimental studies [227]. Furthermore, Fluoxetine injections in rat models enhanced neurogenesis and prevented a pathological increase in stem cell recruitment in the hippocampus [228].…”
Section: Anti-inflammatory Properties Of Antidepressantsmentioning
confidence: 94%